Function of neural stem cells in ischemic brain repair processes - Zhang, Ruilan (J Cereb Blood Flow Metab, 2016)
Hypoxic/ischemic injury is the single most important cause of disabilities in infants, while stroke remains a leading cause of morbidity in children and adults around the world. The injured brain has limited repair capacity, and thereby only modest improvement of neurological function is evident post injury. In rodents, embryonic neural stem cells in the ventricular zone generate cortical neurons, and adult neural stem cells in the ventricular–subventricular zone of the lateral ventricle produce new neurons through animal life. In addition to generation of new neurons, neural stem cells contribute to oligodendrogenesis. Neurogenesis and oligodendrogenesis are essential for repair of injured brain. Much progress has been made in preclinical studies on elucidating the cellular and molecular mechanisms that control and coordinate neurogenesis and oligodendrogenesis in perinatal hypoxic/ischemic injury and the adult ischemic brain. This article will review these findings with a focus on the ventricular–subventricular zone neurogenic niche and discuss potential applications to facilitate endogenous neurogenesis and thereby to improve neurological function post perinatal hypoxic/ischemic injury and stroke.